Bifluoride ([HF2]−) formation at the fluoridated aluminium hydroxide/water interface. Issue 22 (25th February 2016) - Shimizu, Kenichi; Driver, Gordon W.; Lucas, Marie; Sparrman, Tobias; Shchukarev, Andrey; Boily, Jean-François
Abstract : Bifluoride-type species are formed at fluoride-exchanged aluminium hydroxide surfaces contacted with aqueous solutions. First layer surface species are anchors for growth of multi-layered species towards the solution. Abstract : This study uncovers bifluoride-type (difluorohydrogenate(i ); [HF2 ] − ) species formed at mineral/water interfaces. Bifluoride forms at Al–F surface sites resulting from the partial fluoridation of gibbsite (γ-Al(OH3 )) and bayerite (α-Al(OH3 )) particles exposed to aqueous solutions of 50 mM NaF. Fluoride removal from these solutions is proton-promoted and results in a strongly self-buffered suspensions at circumneutral pH, proceeds at a F : H consumption ratio of 2 : 1, and with recorded losses of up to 17 mM fluoride (58 F nm −2 ). These loadings exceed crystallographic site densities by a factor of 3–4, yet the reactions have no resolvable impact on particle size, shape and mineralogy. X-ray photoelectron spectroscopy (XPS) of frozen (−155 °C) wet mineral pastes revealed coexisting surface F − and HF 0 species. Electron energy loss features pointed to multilayer distribution of these species at the mineral/water interface. XPS also uncovered a distinct form of Na + involved in binding fluoride-bearing species. XPS and solid state magic angle spinning 19 F nuclear magnetic resonance measurements showed that these fluoride species were highly comparable to a sodium-bifluoride (NaHF2 ) reference. First layer surface species are represented as Al–F–H–F–Al and Al–F–Na–F–Al, and may form multi-layered species into the mineral/water interface. These results consequently point to a potentially overlooked inorganic fluorine species in a technologically relevant mineral/water interfacial systems.